A thematic literature review on lecturer competency development in religious higher education - Urbanus Sukri (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the development of lecturer competencies in improving the quality of the Tri Dharma of Higher Education in religious universities. The research employs a qualitative approach using a literature review method by analyzing nine selected scientific articles published between 2019 and 2024. Data were collected through documentation techniques and analyzed using thematic analysis to identify key patterns related to lecturer competency development. The findings reveal that pedagogical, professional, digital, and religious competencies play a crucial role in enhancing the implementation of education, research, and community service. Pedagogical competence improves learning quality, while professional competence strengthens research productivity. In addition, digital competence supports innovative and adaptive learning processes, and the integration of religious values enhances the relevance of community service. However, challenges such as limited institutional support, insufficient training, and resource constraints remain significant barriers. This study highlights the importance of a holistic and sustainable competency development strategy to achieve a balanced and high-quality implementation of the Tri Dharma of Higher Education.